Eksplorasi Kerangka Manajemen Risiko Proyek untuk Perusahaan Teknologi Informasi - Isnen Hadi Al Ghozali; Samidi Samidi; Andy Rio Handoko (CogITo Smart Journal, 2023)
Based on CHAOS 2020: Beyond Infinity Overview, reported by the Standish Group, only 31% of  IT projects were successfully implemented, while 50% of projects were challenged and 19% of projects failed. Many project managers less awareness about SRM and have a partial understanding of risk. The purpose of this study is to develop a project risk management framework for listing companies in the information technology sector. The sample for this study is 35 annual reports of technology companies listed on IDX. This study identified 122 types of project risks from 33 companies' annual reports. This study uses an exploratory study approach. The proposed framework includes three stages, namely the root cause, risk assessment, and performance stages. At the root cause stage, the identification of risks from elements of the business environment becomes the basis for measuring risk treatment. In the next stage, the identified risk treatment is measured through identify, analysis, and verification activities with the support of communication, documentation, and evaluation. The measurement results are classified into three major dimensions, namely cost, time, and quality. The final stage of the framework is in the form of residual performance risk and a risk mitigation action plan.